Central-local relations and higher education stratification in China - Yang, P.; R. Wang (Higher Education, 2020)
Regional higher education growth in non-federal states has not attracted much academic attention. This paper is one of the first attempts to explore China's latest higher education expansion and its systematic and regional impact from the perspective of multi-level governance. This article argues that the state had explicitly utilized the Commanding Heights Strategy to diffuse the higher education authority to sub-national level and promote regional growth. The Central authorities allowed the Ministry of Education establishing a vertical elite coalition to command the heights of tertiary institutional hierarchy and key resources for tertiary development. In addition, the state used both financial incentives and sectoral incentives to mobilize resources for regional expansion. The Commanding Heights Strategy shapes China's response to the higher education trilemma of costs, access, and quality. Under this strategy, the unprecedented tertiary expansion has expanded college access, but at the expense of affordability, quality, and a large and increasing regional variation.